Site Classification Based on Shear Wave Velocity from H/V Curve Inversion in Prambanan Subdistrict, Klaten Regency for Earthquake Risk Mitigation - Rahma, Ilqia; Aryono Adhi, Mochamad; Budi Wibowo, Nugroho; Mustami' Limayukha, Desi; Fadlika Widyantari, Elsa; El Farsiyyi, Billqis; Sofyana Ulya, Rahmania (Universitas Negeri Semarang, 2023)
One of the areas that has become a historical tourist attraction in Klaten Regency is Prambanan District. Prambanan District in the south is directly adjacent to Kapanewon Prambanan which has an Opak Fault. This study aims to microzonate earthquake-prone areas based on microseismic parameters using a portable seismograph at 27 measurement points. Data analysis was performed using the Horizontal to Vertical Spectral Ratio (HVSR) method and the ellipticity curve with the help of Geopsy and Dinver software. The results showed that the range of f0 values was between 0.9 and 18 Hz, which was predominantly included in the Type I classification. The A0 values were in the range of 1.2-4 with the size of the distribution of A0 being dominantly low. The value of Kg in this area is classified as low category with a range of 0.1-14. Prambanan District has vs30 values ranging from 234–1260 m/s which are classified into 3 sites namely B, C, and D. The results of this study indicate that Prambanan District has soil with a thick layer of sediment based on information on the distribution of shear wave velocity values to depth 30 meter. These results are relevant as an effort to mitigate earthquake disasters, especially in vulnerable areas such as Prambanan which has a history of seismic activity due to the presence of the Opak Fault.